Superelectrophilic carbocations: preparation and reactions of a substrate with six ionizable groups - Kennedy, Sean H.; Gasonoo, Makafui; Klumpp, Douglas A. (Beilstein Journal of Organic Chemistry, 2019)
A substrate has been prepared having two triarylmethanol centers and four pyridine-type substituent groups. Upon ionization in the Brønsted superacid CF3SO3H, the substrate undergoes two types of reactions. In the presence of only the superacid, the highly ionized intermediate(s) provide a double cyclization product having two pyrido[1,2-a]indole rings. With added benzene, an arylation product is obtained. A mechanism is proposed involving tetra-, penta-, or hexacationic species.
Keywords: cation; Friedel–Crafts; heterocycle; superacid; superelectrophile

(untitled) - Olah, G. A.; Germain, A.; Lin, H. C.; Forsyth, D. A. (J. Am. Chem. Soc., 1975)

(untitled) - Olah, G. A.; Prakash, G. K. S.; Donald, P.; Loker, K. B.; Lammertsma, K. (Res. Chem. Intermed., 1989)

(untitled) - Olah, G. A. (Angew. Chem., Int. Ed. Engl., 1993)

(untitled) - Olah, G. A.; Klumpp, D. A. (Acc. Chem. Res., 2004)

Superelectrophiles and Their Chemistry - Olah, G. A.; Klumpp, D. A. (John Wiley and Sons, 2008)

(untitled) - Olah, G. A.; Lin, H. C. (J. Am. Chem. Soc., 1974)

(untitled) - Olah, G. A.; Lin, H. C. (Synthesis, 1974)

(untitled) - Olah, G. A.; Orlinkov, A.; Oxyzoglou, A. B.; Prakash, G. K. S. (J. Org. Chem., 1995)

(untitled) - Olah, G. A.; Wang, Q.; Orlinkov, A.; Ramaiah, P. (J. Org. Chem., 1993)

Recent Developments in Carbocation and Onium Ion Chemistry - Klumpp, D. A. (Activation of Electrophilic Sites by Adjacent Cationic Groups, 2007)

(untitled) - Naredla, R. R.; Zheng, C.; Nilsson Lill, S. O.; Klumpp, D. A. (J. Am. Chem. Soc., 2011)

(untitled) - Gasonoo, M.; Naredla, R. R.; Nilsson Lill, S. O.; Klumpp, D. A. (J. Org. Chem., 2016)

(untitled) - Newkome, G. R.; Joo, Y. J.; Evans, D. W.; Pappalardo, S.; Fronczek, F. R. (J. Org. Chem., 1988)

Gaussian 09, Revision E.01 (Gaussian, Inc., 2009)